In Situ Investigation of Under-Deposit Microbial Corrosion and its Inhibition Using a Multi-Electrode Array System - Suarez, Erika M.; Lepková, Kateřina; Forsyth, Maria; Tan, Mike Y.; Kinsella, Brian; Machuca, Laura L. (Frontiers in Bioengineering and Biotechnology, 2022)
Carbon steel pipelines used in the oil and gas industry can be susceptible to the combined presence of deposits and microorganisms, which can result in a complex phenomenon, recently termed under-deposit microbial corrosion (UDMC). UDMC and its inhibition in CO2 ambiance were investigated in real-time using a multi-electrode array (MEA) system and surface profilometry analysis. Maps from corrosion rates, galvanic currents, and corrosion potentials recorded at each microelectrode allowed the visualization of local corrosion events on the steel surface. A marine bacterium Enterobacter roggenkampii, an iron-oxidizing, nitrate-reducing microorganism, generated iron deposits on the surface that resulted in pitting corrosion under anaerobic conditions. Areas under deposits displayed anodic behavior, more negative potentials, higher corrosion rates, and pitting compared to areas outside deposits. In the presence of the organic film-forming corrosion inhibitor, 2-Mercaptopyrimidine, the marine bacterium induced local breakdown of the protective inhibitor film and subsequent pitting corrosion of carbon steel. The ability of the MEA system to locally measure self-corrosion processes, galvanic effects and, corrosion potentials across the surface demonstrated its suitability to detect, evaluate and monitor the UDMC process as well as the efficiency of corrosion inhibitors to prevent this corrosion phenomenon. This research highlights the importance of incorporating the microbial component to corrosion inhibitors evaluation to ensure chemical effectiveness in the likely scenario of deposit formation and microbial contamination in oil and gas production equipment.